FINANCIAL QUOTIENT AND LIFE SATISFACTION AMONG EDUCATORS IN THE DISTRICT OF BORONGAN CITY - Hedelisa A.Anguren, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The study aimed to investigate the financial quotient and Life Satisfaction among educators in the District of Borongan City. A descriptive-correlation method of research was utilized in the study. It employed a survey questionnaire to gather information from thirty (30) educators participating in the research investigation. Data collected were subjected to appropriate statistical tools: frequency count, percentage, weighted mean, and Pearson correlation. It was concluded that most of the educators in the district of Borongan City were middle-aged, female, and designated teacher III. Their pastimes were watching TV, using gadgets with the internet, doing household or school chores, and bonding with family and friends. The respondents have a net pay ranging from php5,000.00 to 10,000.00 with financial liability ranging from 100,000.00 and above, not having an extra income. This indicates that the Educators in the district of Borongan City need more education on their finance.